Radiation-/hypoxia-induced solid tumor metastasis and regrowth inhibited by hypoxia-specific upconversion nanoradiosensitizer. (May 2015) - Liu, Yanyan; Liu, Yong; Bu, Wenbo; Xiao, Qingfeng; Sun, Yong; Zhao, Kuaile; Fan, Wenpei; Liu, Jianan; Shi, Jianlin
Abstract: Tumor resistance to ionizing irradiation and cancer cell's metastasis stimulated by radiation often lead to anti-cancer failure, and can be negatively caused by a key role – cellular hypoxia. In this regard, the exploitation of hypoxia-specific cytotoxic agents which assist to potentiate the anti-tumor effect of radiotherapy (RT) as well as efficiently counteract radiation-/hypoxia-induced cancer cell metastasis, becomes especially important, but has been widely overlooked. Herein, a core/shell-structured multifunctional nanoradiosensitizer with upconversion nanoparticle (UCNP) as an inside core, mesoporous silica as the shell and a cavity in between, has been constructed, in which UCNP core serves as radiation dose amplifiers and bio-reductive pro-drug – tirapazamine (TPZ) loaded in cavity is an hypoxia-selective cytotoxin and the silica shell provides the protection and diffusion path for TPZ. Such nanoradiosensitizer has been employed to inhibit the hypoxia-reoxygenation and the subsequent replication of cancer cells that often occurs after a single unaccompanied RT at low doses, and to silence the expression of transcription factors that support the progression of malignancy in cancer. This study confirms the radiotherapeutic benefits of utilizing nanoradiosensitizer as adjuvant to low-dose RT, and the results demonstrate the highly efficient hypoxia-specific killing in oxygen-dependent anti-tumor therapies.